The utilization and management of selected listed-threatened or protected species in the Limpopo Province, South Africa - Rasethe, Marula Triumph (My University, 2017)
In South Africa, the harvesting of indigenous plants has been taking place for centuries, and people in rural areas still rely on them to meet their primary health care needs. In the Limpopo Province, this traditional medicine is based on various plant resources, including those that are protected by legislation, such as the Threatened or Protected Species (TOPS) Regulations promulgated in terms of the National Environmental Management: Biodiversity Act (NEMBA) of 2004. Despite a number of ethnobotanical studies conducted in this province, which briefly highlighted the overutilization of some of the TOPS-listed plants, there has been no detailed study that focused on the use and management of these plant species. This study was conducted to document the different uses, threats, local management strategies and approaches to conserving these plant species. The study was conducted in the Capricorn, Sekhukhune, Mopani, Waterberg and Vhembe districts of the Limpopo Province. Six TOPS-listed species occurring in the Province were selected after a pilot study based on their occurrence in the Province, familiarity with participants and known vernacular name. These species included Alepidea amatymbica Eckl. & Zeyh, Brackenridgea zanguebarica Oliv, Dioscorea sylvatica Eckl, Drimia sanguinea (Schinz) Jessop, Siphonochilus aethiopicus (Schweinf.) B.L.Burtt and Warburgia salutaris (G.Bertol.) Chiov. Information was collected from 180 traditional healers, 110 community members, 26 traditional leaders and 15 conservation officers, using semi-structured questionnaires, supplemented with field observations. Results indicated that the selected species are used by traditional healers and community members exclusively for medicinal purposes. Preferences were predominantly for D. sanguinea, S. aethiopicus and W. salutaris. Remedies were most often prepared using the underground parts of the plants, which were chiefly purchased from muthi shops or markets trading both indigenous and exotic plant and animal materials used for witchcraft and/or healing. Just over 59% of respondents indicated that they purchase materials from muthi shops due to the scarcity and thus unavailability of some species in local communal lands (open access lands). In contrast nearly 40% of participants (traditional healers and community members) disclosed that they harvest materials from open access land. Only 1.49% of participants (traditional healers and community members) sourced from their homegardens; cultivating D. sanguinea and S. aethiopicus for both proximity (quick access) and easy harvesting. Generally, participants (82%) who did not cultivate these species, however, indicated an interest to cultivate if seed/seedlings were to be provided. An analysis of participants’ perceptions regarding factors threatening the survival of these species revealed that they (93%) viewed overharvesting for medicinal use as the most significant threat. During field visits, it was observed that the degree of impact due to harvesting on populations of these species was very high. This was exacerbated by destructive harvesting techniques by collectors, including uprooting of herbaceous species such as A. amatymbica, D. sylvatica, D. sanguinea and S. aethiopicus. Woody tree species, particularly W. salutaris, were sometimes felled for easy harvesting of stem bark. Most (65.86%) of the community members and traditional healers revealed that there was nobody managing plants on communal lands, and therefore no conservation strategies are in place. However, a minority of participants indicated that chiefs (16.55%), chiefs and indunas (senior officials appointed by the king or chief, who often act as a bridge between the people and the chief) (14.83%), government (2.07%) and indunas (0.69%) are responsible for the management of plants in their areas. Community members, traditional healers and traditional leaders mentioned that there are general community rules for conserving plants, but these mostly focused on trees used for fuelwood. Similarly, conservation officers indicated that in most cases they patrol in rural areas for fuelwood use monitoring rather than medicinal plants, because they were unable to identify medicinal plant use impact during their patrols. The study concludes that TOPS-listed plants are unsustainably harvested for medicinal purposes in the Limpopo Province, and without adequate control or management of the resource. This is due to a limited knowledge regarding conservation by harvesters, users, community leaders and elders, as well as unsustainable harvesting by collectors. Consequently, this study recommends that effective conservation measures are urgently needed to prevent further loss of most of these species in the natural environment. It is proposed that a workshop to educate harvesters, traditional leaders and conservation officers regarding the TOPS-listed species be held. An identification guide for conservation officers should also be compiled, to be used during field patrols. Furthermore, practical skill development should be provided to people who currently cultivate at home or have expressed interest in cultivating TOPS species. Institutions such as SANBI could play an enabling role in providing seed/seedlings for home cultivation. Traditional leaders should furthermore be encouraged to work with government agencies (e.g. SANBI, LEDET, DEAT) in implementing and strengthening traditional rules that apply to medicinal plants.
Thesis (M.Sc. (Botany)) -- University of Limpopo, 2017
Keywords: Endangered plants; Indigenous plants; Traditional medicine; Endangered plants; Endangered species -- South Africa; Endemic plants; Traditional medicine -- South Africa